2021
DOI: 10.53022/oarjbp.2021.2.2.0045
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and sensory parameters of cashew apple jam (Anarcadium occidental L.) harvested in Bondoukou area (North East, Côte d’Ivoire)

Abstract: In Côte d'Ivoire, cashew apples represent waste in plantations due to lack of processing. This study deals with their transformation into jam for a better valorization. Cashew apple jam were analyzed for physicochemical and sensory properties. Proximate physiochemical were determined using standard analytical procedures and the sensory acceptance test was performed by 50 panelists on the following attributes. Proximate result showed that moisture content of cashew apple jam was 26.5±1.77% ; carbohydrate 67.7±0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…85 Cashew can also be processed into products like jam and marmalades. Studies 86,87 have demonstrated that cashew apple jam is a good source of nutrients, phytochemicals, and energy. Nonetheless because the jam involves the use of the juice, Figueroa-Valencia et al 88 proposed the use of the apple pulp in making marmalade, due to the high phenolic content of the pomace.…”
Section: Processing and Value-addition Of Cashew Applementioning
confidence: 99%
“…85 Cashew can also be processed into products like jam and marmalades. Studies 86,87 have demonstrated that cashew apple jam is a good source of nutrients, phytochemicals, and energy. Nonetheless because the jam involves the use of the juice, Figueroa-Valencia et al 88 proposed the use of the apple pulp in making marmalade, due to the high phenolic content of the pomace.…”
Section: Processing and Value-addition Of Cashew Applementioning
confidence: 99%